Pengaruh Pembiasaan Ibadah dan Keteladanan Guru terhadap Kecerdasan Emosional Siswa Madrasah Ibtidaiyah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study examines the predictive influence of religious habituation and teacher role modeling on students’ emotional intelligence in an Islamic elementary school context. A quantitative approach with an ex post facto design was employed, involving 78 students selected through total sampling. Data were collected using Likert-scale questionnaires and analyzed using multiple linear regression. The findings indicate that religious habituation has a positive and significant effect on students’ emotional intelligence, while teacher role modeling demonstrates a relatively stronger contribution. Simultaneously, both variables significantly predict emotional intelligence, explaining 74.9% of its variance. These results suggest that students’ socio-emotional development is shaped by the integration of structured religious practices and pedagogical modeling within the school environment. The study contributes to the ecological-religious perspective on character education by emphasizing the importance of consistent spiritual habituation and teachers’ personal competence in fostering emotional regulation and social skills. Practically, Islamic elementary schools are encouraged to strengthen religious culture programs and support teachers’ emotional and moral development to enhance students’ emotional intelligence.